Fikrah Tajridiyyah Ash-Shathahat Ash-Shufiyah 'Inda As-Siraj Ath-Thusi. - Fahad Aminudin (Jurnal Hikmatuna, 2016)
Undoubtedly, Sufism is a way of life that is often difficult to express to others in detail because it involves emotional states that are hard to comprehend. Among these are the surprising statements made by Sufis during intense spiritual experiences, which they refer to as "shathahat" (ecstatic utterances). Some individuals reject these statements, and some even consider the speakers as blasphemous. The discussion of shathahat is not new within Sufism. Abu Nasr as-Sarraj at-Tusi, who lived in the 4th century AH, presents a theory of shathah and explores its attractive aspect that can be understood by devoted seekers on the spiritual path. It could be an expression or a form of representation for such ecstatic utterances. Notably, he addresses these interpretations in his book "al-Luma'" regarding the shathahat of the Sufis, providing responses to those who reject such statements, emphasizing that although their outward appearance may seem irrational, their inner truth remains valid and upright. From this, it can be inferred that according to as-Sarraj at-Tusi, shathahat is an expression used by Sufis to depict and describe their intense spiritual experiences when they are overwhelmed by divine power and passion. He perceives an agreement in defining "wujd" (ecstasy) among Sufis as the secret of Allah revealed to the believers who possess certainty, suddenly entering their hearts. Understanding the experience of wujd, characterized by intense passion and overpowering fervor, is only possible through grasping the underlying meaning that as-Sarraj at-Tusi comprehends, similar to these shathahat. Keywords: as-Sarraj at-Tusi, shathahat, al-Luma'.